Estudio del efecto de la variación de amina (dietilentriamina (DETA) y trietilentetramina (TETA)) y la concentración en el crecimiento de microcápsulas en el tiempo (2017)
"The main objective of the project was to study the effect on time of varying the amine and the concentration of the same in the growth of microcapsules. The above, in order to obtain results that contribute to determine the effects of making these modifications in the process and product for the future development of a microencapsulated agrochemical. The preparation of the capsules was made by the interfacial polymerization of MDI PAPI 27 polymer with triethylenetetramine (TETA) and diethylenetriamine (DETA), to encapsulate xylene. The size of particle, or in this case the size of the microcapsules was measured with the Mastersizer 3000, with samples taken at intervals of time, and then observed under a microscope, in order to compare the results obtained in both equipment and to analyze the formation of the microcapsules." -- Tomado del Formato de Documento de Grado.